FeOx@GAC catalyzed microbubble ozonation coupled with biological process for industrial phenolic wastewater treatment: Catalytic performance, biological process screening and microbial characteristics - DENG SHIHAI (2020)
https://doi.org/10.1016/j.watres.2020.116687